Kidney transplantation in children and adolescents with C3 glomerulopathy or immune complex membranoproliferative glomerulonephritis: an International survey of current practice - Patry, Christian; Webb, Nicholas; Meier, Matthias; Pape, Lars; Fichtner, Alexander; Höcker, Britta; Tönshoff, Burkhard (Pediatric transplantation, 2025)
Background Approximately 50% of patients with chronic kidney disease due to C3 glomerulopathy (C3G) or primary immune-complex membranoproliferative glomerulonephritis (IC-MPGN) will require dialysis and/or kidney transplantation (KTx) within the first 10 years of disease onset. Currently, there are no guidelines regarding the indications for KTx or post-transplant management. Methods We therefore initiated an international online survey via Survey Monkey on C3G and IC-MPGN in children with CKD stage 5. All KTx centers of the European Society for Paediatric Nephrology (ESPN) were invited to participate in the survey, which was conducted from August 23 to November 25, 2023. Results Sixty-five (63%) of the centers (n = 103) participated. Twenty-six percent had made at least one decision against living donation for a child with C3G or IC-MPGN. The main reason for 88.2% of these decisions was concern about the recurrence of the underlying disease in any potential transplant. Eighty-eight percent indicated deceased donation as an option; 12% decided not to proceed with transplantation at all. Regarding KTx decision-making or management, none of them referred to an existing recommendation by any national or regional guideline. For the recurrence of C3G or IC-MPGN post-transplant, eculizumab treatment was suggested by 60% of respondents. Conclusion This survey shows a considerable reluctance of pediatric nephrologists to list patients with CKD stage 5 due to C3G or IC-MPGN for living donor kidney transplantation. This decision is mainly based on the fear of recurrence of the underlying disease combined with the lack of reliable treatment options. This limited access of affected patients to the best treatment option for kidney failure requires further action.